2012
DOI: 10.3109/10673229.2012.649113
|View full text |Cite
|
Sign up to set email alerts
|

Relevance or Excellence? Setting Research Priorities for Mental Health and Psychosocial Support in Humanitarian Settings

Abstract: Background: Humanitarian crises are associated with an increase in mental disorders and psychological distress. Despite the emerging consensus on intervention strategies in humanitarian settings, the field of mental health and psychosocial support (MHPSS) in humanitarian settings lacks a consensus-based research agenda. Methods: From August 2009 to February 2010, we contacted policymakers, academic researchers, and humanitarian aid workers, and conducted nine semistructured focus group discussions with 114 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 32 publications
0
52
0
3
Order By: Relevance
“…(#7) and 'To what extent do current mental health and psychosocial supports address locally perceived needs?' (#9) (Tol et al, 2011c(Tol et al, , 2012.…”
mentioning
confidence: 99%
“…(#7) and 'To what extent do current mental health and psychosocial supports address locally perceived needs?' (#9) (Tol et al, 2011c(Tol et al, , 2012.…”
mentioning
confidence: 99%
“…Only 6% of the 733 generated research questions concerned traumatic stress. Furthermore, the final top 10 most highly prioritised research questions from this study – with over 80% agreement that these questions were ‘essential’ to address in the coming 10 years – included six questions relevant to problem analysis and assessment 9 10. In addition to a focus on a broader range of mental disorders and psychosocial issues, the resulting research agenda emphasises the inclusion of perspectives from affected populations and sensitivity to socio-cultural issues in defining mental health and psychosocial problems, needs and capacities in humanitarian settings.…”
Section: Mhpss Needs Assessmentmentioning
confidence: 99%
“…Two research priority setting activities have been undertaken in recent years for mental health, one by members of the Lancet Mental Health Group (11) and another by the Mental Health and Psychosocial Support in Humanitarian Settings-Research Priority Setting project (12). These have highlighted the need for better alignment between researchers and practitioners, and concluded that it would be best to fill critical knowledge gaps by investing in research into 3 areas: health policy and systems; epidemiology; and improved delivery of cost-effective interventions.…”
Section: Prioritizationmentioning
confidence: 99%
“…The criteria developed by the Lancet Mental Health Group (11) and the Mental Health and Psychosocial Support in Humanitarian SettingsResearch Priority Setting project (12) can be used by the EMR to develop specific priorities. The steps used by the Lancet group were:…”
Section: Adopt a Prioritized National Mental Health Research Agendamentioning
confidence: 99%